Lsp1 partially substitutes for Pil1 function in eisosome assembly under stress conditions - Vesela, Petra; Zahumensky, Jakub; Malinsky, Jan (Journal of cell science, 2023)
Eisosomes are large hemitubular structures that underlie the invaginated microdomains in the plasma membrane of various ascomycetous fungi, lichens and unicellular algae. In fungi, they are organized by BAR-domain containing proteins of the Pil1 family. Two such proteins, Pil1 and Lsp1, participate in eisosome formation in the yeast Saccharomyces cerevisiae. Under normal laboratory conditions, deletion of the PIL1 gene results in the inability of cells to assemble wild-type-like eisosomes. We found that under certain stress conditions, Lsp1 partially substitutes for the Pil1 function and mediates assembly of eisosomes, specifically following a decrease in the activity of serine palmitoyltransferase, for example, in response to hyperosmotic stress. Besides Lsp1, the assembly of eisosomes lacking Pil1 also requires Seg1 and Nce102 proteins. Using next-generation sequencing, we found that the seg1Δnce102Δpil1Δ strain, which is unable to form eisosomes, overexpresses genes coding for proteins of oxidative phosphorylation and tricarboxylic acid cycle. By contrast, genes involved in DNA repair, ribosome biogenesis and cell cycle are downregulated. Our results identify Lsp1 as a stress-responsive eisosome organizer and indicate several novel functional connections between the eisosome and essential cellular processes.
Keywords: Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; Pil1; membránové proteiny; Saccharomyces cerevisiae Proteins; Membrane Proteins; Cell Membrane; Membrane compartment of Can1; fosfoproteiny; Lsp1; Sphingolipid; Phosphoproteins; Stress; Eisosome; buněčná membrána